(untitled) (Research, Society and Development, 2022)
The Youth and Work dossier, organized by the Revista Novos Estudos, is one of the most current, complete, and important collections of studies that address the relationship between youth and the world of work. It had its elaboration at the beginning of the advance of the pandemic in Brazil. In view of this, our objective is to raise discussions that support the dialogue between the notes presented in the dossier and the set of data released by the Brazilian Institute of Geography and Statistics (IBGE) on unemployment rates in Brazil. To achieve this objective, we raise the following question: how do the results presented in the Youth and Work dossier dialogue with data on unemployment in the pandemic context of 2020 and 2021? The methodology of construction of this article is of a theoretical-bibliographic nature, interspersed with description and statistical analysis of secondary data and examination of the articles that make up the dossier. According to our results, there is an asymmetry between the theses defended in the analysed articles and the data that trigger a high rate of young people without work in the pandemic context. The article concludes that the reality that gives rise to a conjunction between the economic crisis and the health crisis exacerbates the inequalities in the inclusion of young people in the world of work. Finally, we hope that the proposed analysis can support a qualitative correlation of data from current research that points to inequalities in the transition from school to work, identifying the need for public policies aimed at education and insertion in the labour market of young people who transition into adulthood.